Optic Nerve Involvement in Retinoblastoma: Role of Computed Tomography with and without Contrast - Muhammad Zubair, Mughese Amin, Soufia Farrukh, Faroohi Saghir (Pakistan Journal of Ophthalmology, 2009)
Purpose: The study was designed to evaluate the role of contrast enhanced CT scan as a non invasive test in the detection of optic nerve involvement in retinoblastoma. Material and Methods: This retrospective study was conducted in Bahawal Victoria Hospital, Bahawalpur over a period of one year. 19 consecutive retinoblastoma patients underwent CT scan without and with I/V contrast. If the central retinal vessels were subjectively visualized with I/V contrast the optic nerve (ON) was considered to be free of RB. 19 enucleated globes were also sent for histopathology, all the optic discs and nerves examined for presence or absence of tumor and the level of involvement. Results: The correlation between visualization/enhancement of central retinal vessels and the presence or absence of optic nerve involvement histopathologically was found to be significant. (p=0.0006, Fisher exact test). Conclusion: In high spatial resolution enhanced CT with 1.5mm sections, non visualization of central retinal vessels reliably indicates optic nerve involvement with retinoblastoma.